2022
DOI: 10.1101/2022.07.12.499711
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Macroscopic and microscopic study on floral biology and pollination of Cinnamomum verum Blume (Sri Lankan)

Abstract: Cinnamomum verum Blume (syn Cinnamomum zeylanicum) commonly known as Ceylon cinnamon, has gained worldwide attention and well supported by experimental data. Maintaining the yield quality and quantity are essential, especially for high-end value-added products. Breeding superior varieties and producing good quality planting materials are critical for commercial cultivation efforts. However, limited literature is available on the floral development and biology of C. verum. We assessed the seasonal flowering, … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…The current analysis suggests comparatively higher nucleotide diversity in the trn H- psb A and pet A- psb J regions than in the common universal barcoding regions. However, a previous study has also reported inadequacy of the nucleotide diversity in the trn H- psb A region for molecular level identification of the Cinnamomum species in Sri Lanka [ 5 ]. The current work proposes new barcode regions of ycf1 , ITS and mitochondrial genes of atp6 and cox 1 for the identification of Cinnamomum species.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The current analysis suggests comparatively higher nucleotide diversity in the trn H- psb A and pet A- psb J regions than in the common universal barcoding regions. However, a previous study has also reported inadequacy of the nucleotide diversity in the trn H- psb A region for molecular level identification of the Cinnamomum species in Sri Lanka [ 5 ]. The current work proposes new barcode regions of ycf1 , ITS and mitochondrial genes of atp6 and cox 1 for the identification of Cinnamomum species.…”
Section: Discussionmentioning
confidence: 99%
“…However, the Scanning Electron Microscopic analysis (SEM) of C . verum (Sri Lanka) pollen samples [ 5 ] suggests considerable differences compared to recently published SEM data of C . verum (India) [ 99 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations